INFORMATION SOCIETY AND TRANSFORMATION ACTIVITIES OF LIBRARIES OF HIGHER EDUCATION INSTITUTIONS - Lukjanenko, Viacheslav V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article deals with the transformation of information and libraries of higher educational institutions of Ukraine. Some attention is given to the deployment process mediatization information environment and their impact on society.